Organogenesis in meristems and cauline disc of Aloe vera L. - Albarrán Ruiz, Yuri; Pacheco Maldonado, José Constantino; Rache Cardenal, Leidy Yanira (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Aloe vera L. has been used as a medicinal plant and ornamental, so that this plant has acquired great commercial importance. However, A. veraL. has a reproductive disadvantage under natural conditions limiting supply of world demand. The objective of this study was evaluated process organogenesis development from meristematic tip and cauline discs. Meristematic tip and cauline discs were used as explants and cultured on Murashige and Skoog medium supplemented with different growth regulators. The percentage of organogenic and callogenic induction was quantified. Regenerated shoots were micropropagated on medium supplemented with 2 mg L-1BA and 0.1 mg L-1NAA, and rooting was tested under in vitroand ex vitroconditions.Highest percentage of callus formation in meristematic tip was quantified in presence of 0.5 and 1 mg L-12,4-D and 3 mg L-1NAA and in cauline disks in presence of 0.5 mg L-1of 2,4-D. During caulogenesis, highest average number of shoots per explant (1.1) was quantified from meristematic tip in presence of 5 mg L-1NAA, while in cauline disk (1.3 shoots/explant) were quantified in presence 0.25 mg L-12,4-D. After micropropagation cycle second, the average number of shoots per explant increased to 8.8. The highest percentage (75.3%) of rooted shoots was quantified in vitroconditions. In conclusion, the primary explant more desirable to initiate organogenic processes in A. verawas meristems cultured in medium with 5.0 mg L-1NAA.